Automotive Ergonomics: Passenger Cars Interior Dimension Parameters and Comfort - Zamri, Mohamed (2007)

(untitled)
Abstract— Automotive ergonomics is the study of how automotive can be designed better for human use. The human factor aspect of designing automobiles is first considered at the Vehicle Packaging stage. The term Vehicle Packaging comes to use whenever a new model is in the early stage of study. It is a method to safeguard and protect space for the human user and necessary components that make up the vehicle being designed. Other purposes are to provide alternative solutions and proposals, to ensure the legal requirements are met and to ensure all inhouse requirements are met. This study is to correlate automobiles interior dimensions to comfort factors by means of measuring and survey as well as using ergonomic software. Four cars are compared to achieve this objective. From the result, it can be seen that dimension factors of interior affects the car ergonomic factors. By looking into specific dimension parameters, one can see the differentiation between all four cars. For driver's comfort as well as reach factors, survey shows majority respondents prefer Honda City and Toyota Vios. However from discomfort assessment using Ramsis, it was suggested that both Proton cars gives better comfort for taller population while Honda City and Toyota Vios gives better comfort for shorter population. Other factors evaluated were driver clearance and spaciousness, driver seat and steering adjustability, driver reach ability to surrounding components, driver view (inside and outside), front and rear door entry / exit, rear passenger spaciousness and view, vibration and noise, and trunk space.